(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
During almost two centuries of the formation and development of the world industrial society, the economies of many countries experienced crises, during which there was a growing decline in production, the accumulation of unsold goods on the market, falling prices, the collapse of the mutual settlement system, the collapse of banking systems, the ruin of industrial and trading firms a sharp jump in unemployment.